Diversity of Aspergillus, Penicillium, and Talaromyces Species Isolated from Freshwater Environments in Korea. Issue 1 (2nd January 2019) - Heo, Inbeom; Hong, Kyeongyeon; Yang, Hyejin; Lee, Hyang Burm; Choi, Young-Joon; Hong, Seung-Beom
Abstract: In order to elucidate the fungal diversity and community structure in freshwater environments, numerous fungal strains were isolated from freshwater, submerged soils, twigs, dead insects, etc. Among them, the present study has focused specifically on Aspergillus, Penicillium, and Talaromyces species, which produce diverse useful metabolites in general. Twelve strains of Aspergillus isolated were identified as A. japonicus ( n = 5), A. tubingensis (3), A. niger (2), and A. flavus (2), 10 strains of which belong to Aspergillus section Nigri, named black Aspergillus . Eight strains of Penicillium were identified as P. brasilianim ( n = 3), P. oxalicum (2), P. crustosum (1), P. expansum (1), and P. piscarium (1). Two different strains of Talaromyces were identified as T. pinophilus and T. versatilis . Thus far, Penicillium piscarium and Talaromyces versatilis have been unrecorded in Korea, for which we provide detailed morphological and molecular characteristics.